Some aspects of plant symbolism in Indian civilization - Alberto Pelissero (Kervan. International Journal of Afro-Asiatic Studies, 2016)
A bird’s eye review of a few significant features of plant symbolism in Indian world, both in priestly and in buddhistic milieu: tree as axis mundi (the reversed tree, aśvattha, Ficus religiosa); bodhi tree in buddhistic context; the myth of the birth of human beings from vegetables (Lagenaria vulgaris) in the Rāmāyaṇa; the rice and the chaff (in relation with the law of retribution of acts) in the Paramārthasāra by Abhinavagupta; the celestial desire-fulfilling creeper (kāmavallī) and the transformation of the celestial nymph Urvaśī into a creeper. Within brahmanical tradition a significant range of sources is used, mainly Vedas, upaniṣads, Bhagavadgītā and purāṇas.